Aplikasi Perhitungan Pajak Reklame Di Dinas Pendapatan Daerah Kabupaten Bandung Barat - Komarudin Komarudin; Mia Amalia (Jurnal Computech & Bisnis (e-Journal), 2016)
The purpose of this study to make an application advertisement tax calculation in the Dispenda Kabupaten Bandung Barat. Currently the data processing is still done manually which caused some problems and there are also obstacles such calculations fast enough so that takes a long time in the process poses. Therefore it needs to make an application that can handle these problems. To achieve these objectives need to be done in the following steps of conducting systems analysis, design and implement advertising tax calculation application. Through this application is expected to support to simplify the calculation of local taxes and can accelerate employee in performing his job duties. Keywords: application; advertisement tax.